CHANGING PATTERNS OF HEART DISEASE COMPLICATING PREGNANCY IN THE UNIVERSITY OBST & GYNAE UNIT, COLOMBO - Wijeratne, C N; Kaluarachchi, A; Perera, R M S; Seneviratne, H R (My University, 2012)
OBJECTIVE : TO STUDY THE CHANGES IN THE PATTERN OF HEART DISEASE IN PREGNANCY OVER THE PAST FOUR DECADES IN A SRI LANKAN CENTRE. METHOD : The data of pregnant mothers with heart disease attending the University Obst & Gynae Unit frem '93—'97 were analyzed prospectively. Echocardiography was performed on al l subjects; cardiac and Obstetric complications and pregnancy outcome were recorded. The data was compared with that published from the same clinical department over the past four decades. RESULTS : In the decades 1 50c -'60s and '70s the * incidence was less than 1% while i t was 2.01% and 2.5% in the '80s and '90s respectively. MVP has been recognized from the '80s and caused a decline in the prevalence of rheumatic heart disease from 74% in '70s to 51% in the '80s . Rheumatic heart disease however showed an independant decline throughout the study period. Maternal deaths were absent in the '60s and '70s while in the '80s i t has been 1.7% and 1.3% in the last two decades. This is due to a higher rate of pregnancy in women with very serious heart disease. CONCLUSIONS : Future programs should include screening in adolescence and premarital and pre-pregnancy councelling